2010
DOI: 10.1007/s00417-010-1315-z
|View full text |Cite
|
Sign up to set email alerts
|

A review of clinical trials of anti-VEGF agents for diabetic retinopathy

Abstract: For diabetic macular edema, phase II trials of intravitreal pegaptanib and intravitreal ranibizumab have shown short-term benefit in visual acuity. Intravitreal bevacizumab also has been shown to have beneficial short-term effects on both visual acuity and retinal thickness. For proliferative diabetic retinopathy (PDR), early studies suggest that intravitreal bevacizumab temporarily decreases leakage from diabetic neovascular lesions, but this treatment may be associated with tractional retinal detachment (TRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
150
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(155 citation statements)
references
References 83 publications
3
150
0
2
Order By: Relevance
“…[2][3][4]8,9,62 There are several reports of development or progression of tractional retinal detachment (TRD) after intravitreal injection of bevacizumab before vitrectomy for advanced proliferative diabetic retinopathy (PDR). [63][64][65] In a retrospective series, 5.2% of eyes developed or had progression of TRD following injection.…”
Section: Adverse Events Following Intravitreal Anti-vegf Injections: mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4]8,9,62 There are several reports of development or progression of tractional retinal detachment (TRD) after intravitreal injection of bevacizumab before vitrectomy for advanced proliferative diabetic retinopathy (PDR). [63][64][65] In a retrospective series, 5.2% of eyes developed or had progression of TRD following injection.…”
Section: Adverse Events Following Intravitreal Anti-vegf Injections: mentioning
confidence: 99%
“…Intravitreal injection of anti-vascular endothelial growth factor (anti-VEGF) agents have revolutionized the treatment of common retinal diseases, including neovascular age-related macular degeneration (AMD), 1 diabetic retinopathy, 2 and retinal vein occlusions (RVOs). 3 Moreover, promising results were reported with intravitreal injection of anti-VEGF agents for other ocular diseases, such as neovascular glaucoma, 4 retinopathy of prematurity (ROP), 5 and intraocular tumors.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative treatment approach, and to now, available for less than a decade, is the use of intravitreal therapies targeting VEGF (Nicholson & Schachat, 2010), the most potent known promoter of vascular permeability (Senger et al, 1990). Clinical studies have established that VEGF concentrations are elevated in eyes with DME (Funatsu et al, 2003;Funatsu et al, 2005), and preclinical studies have demonstrated that VEGF levels increased after its onset in a manner temporally correlated with the breakdown of the blood-retinal barrier (Qaum et al, 2001).…”
Section: Anti-vascular Endothelial Growth Factor (Anti-vegf) Injectionmentioning
confidence: 99%
“…Microvascular complications are retinopathies, nephropathies and neuropathies while macrovascular complications include myocardial infarctions, hypertension and peripheral arterial diseases [2]. In this paper, we focus on damages caused to the retina by the complications associated with diabetes mellitus; the leading cause of vision loss in working-age individuals worldwide [3].…”
Section: Introductionmentioning
confidence: 99%
“…Also, retinal endothelial cells have a high number of VEGF receptors that increase in patients with diabetes [4]. VEGF contribute significantly to the development of Diabetic macular edema (DME) by affecting the tight junctions of endothelial cells in the retina by increasing leukocyte count and these leukocytes are known to cause leakage [3]. This causes the breakdown of the blood-retinal barrier and the accumulation of fluid in the macula [5] which in turn will result in reduced or distorted vision.…”
Section: Introductionmentioning
confidence: 99%